(untitled) (Education in the 21st Century, 2023)
The article examines the issue of improving the professional training of future specialists with innovative technologies in physical education classes. It is highlighted that the main principles of professional training are a systemic, personally oriented approach, the main concept of which is the system as a whole, in which the educational process is considered as a stable set of interdependent elements (subsystems: didactic, educational, methodical, social) and interconnected actions in them. Their joint functioning is aimed at educating healthy students with a high level of physical fitness and acquired knowledge, abilities and skills for independent physical exercises. It is theoretically substantiated that physical education focuses on the development of the student as a personality, individuality and an active subject of professional training, which can be implemented only on the humanistic-democratic basis of pedagogical activity. Such an organization of professional training of future specialists increasingly acquires the character of dialogue, cooperation, co-creation, in which the mutually interested exchange of experiences of the teacher and the student prevails. This provides wider opportunities for students to prepare to meet the requirements of the future profession, the success of self-realization in which will be determined both by his professional knowledge and acmeological factors of life, attitude to the health of his and subordinates. The physical culture of a person reflects his education, physical fitness and perfection, which are achieved on the basis of the use of physical education. Physical education in the construction of the system of self-realization of the individual acts as a subject of self-improvement and involvement in the values of physical culture and is aimed at the object of improvement and development - the personality of the student. Therefore, physical education, as an educational discipline, reflects the level of education, physical and mental capacity, the formation of a culture of health based on the use of means and methods of physical education. Thus, the introduction of innovative technologies and their elements in the educational environment allow, to a greater extent, to solve the tasks of physical education, to increase interest in physical education, to satisfy motor activity, to increase the level of health and the development of physical qualities.